Penggunaan beberapa cendawan endofit untuk menekan penyakit layu pada jahe (Zingiber officinale Rosc.) di lahan gambut - Suswanto, Iman; Ramadhan, Tris Haris (Universitas Muhammadiyah Mataram, 2022)
Efforts to overcome R. solanacearum which causes bacterial wilt (BW) in ginger in peatlands are through a strategy to suppress the initial population. One of the efforts is to use endophytic fungi (CE) as biological control agents. This study aims to examine the use of several endophytic fungi isolates from pepper to suppress bacterial wilt disease and improve the growth of ginger. The treatment of CE biological agents in the form of Aspergillus spp., Fusarium sp., T. harzianum, and T. viride to suppress wilt disease in vivo and the use of biological agents as biofertilizers in the field. The source of the pathogenic bacterium P. solanacearum was obtained from samples of wilted rhizomes from community ginger field isolated on NA media. This study was arranged based on a completely randomized design with five replications. The research variables were wilt disease severity, plant height, number of leaves, number of stems, stem diameter & rhizome weight. The results showed that R. solanacearum caused symptoms after an incubation period of 9 days after inoculation. The four CE isolates were able to suppress the symptoms of ginger wilt in the range of 70-80%. The use of CE isolate was also able to improve the growth of ginger, but it has not been followed by an increase in the production of ginger rhizomes. It is suggested that the use of CE as a biofertilizer needs to be increased in the frequency of its application.